Iran. La communauté internationale doit se tenir au côté des femmes et des filles qui souffrent de l’intensification de l’oppression - Amnesty International (Amnesty International, 2023)
Les autorités en Iran intensifient considérablement la répression des femmes et des filles iraniennes qui défient la législation imposant le port du voile.
Keywords: 2023-07 July

Tunisia: Human rights at risk two years after President Saied’s power grab - Amnesty International (Amnesty International, 2023)
In the second year since Tunisian President Kais Saied’s power grab, Tunisian authorities have taken further steps towards repression by jailing dozens of political opponents and state critics, violated the independence of the judiciary, dismantled institutional human rights safeguards, and incited discrimination against migrants, Amnesty International said today. “Decree by decree, blow by blow, President Saied and his government have dramatically undermined respect for human rights in Tunisia since his power grab in July 2021. In doing so, he has stripped away basic freedoms that Tunisians fought hard to earn and fostered a climate of repression and impunity. The Tunisian authorities must immediately reverse this treacherous trajectory and uphold their international human rights obligations,” said Heba Morayef, Amnesty International’s Regional Director for the Middle East and North Africa.
Keywords: 2023-07 July; Kaïs Saïed

Soudan. Les pays voisins doivent assurer le passage en toute sécurité des personnes fuyant le conflit - Amnesty International - Amnesty International (Amnesty International, 2023)
Les pays limitrophes du Soudan doivent immédiatement lever les restrictions d’entrée pour ceux qui fuient le conflit dans le pays et garantir l’accès à la protection et à la sécurité aux plus de 500 000 personnes qui ont déjà fui les combats, a déclaré Amnesty International le 6 juillet 2023.
Keywords: 2023-07 July

Sudan: Neighbouring countries must provide safe passage to those fleeing conflict - Amnesty International (Amnesty International, 2023)
Between 9 May and 16 June, Amnesty International interviewed 29 civilians faced with the difficult choice of whether to return to the conflict they fled, or remain stranded at the border, where they may wait for an indefinite period without basic supplies to maintain their health, privacy, and dignity.
Keywords: 2023-07 July

Iran: International community must stand with women and girls suffering intensifying oppression - Amnesty International (Amnesty International, 2023)
The Iranian authorities are doubling down on their oppressive methods of policing and severely oppressing Iranian women and girls for defying degrading compulsory veiling laws, Amnesty International said today. In a detailed analysis published today, the organization exposes the authorities’ intensified nationwide crackdown on women and girls who choose not to wear headscarves in public.
Keywords: 2023-07 July

Viet Nam: Drop charges and immediately release activist sentenced to six years in prison - Amnesty International (Amnesty International, 2023)
“The unfair charges and inhumane prison conditions shows the Vietnamese authorities’ willingness to systematically silence dissent in direct violation of international human rights law."
Keywords: 2023-07 July

Pays-Bas. La loi a été modifiée pour reconnaître qu’un rapport sexuel sans consentement est un viol : une «victoire historique» - Amnesty International (Amnesty International, 2023)
« L’adoption de ce projet de loi est une victoire historique pour les victimes de violences sexuelles.
Keywords: 2023-07 July

Cambodge. L’élection se déroule sous la menace d’une crise des droits humains - Amnesty International (Amnesty International, 2023)
La répression contre les droits fondamentaux dans le pays s’intensifie.
Keywords: 2023-07 July

Viêt-Nam. Il faut que le militant condamné à six ans d’emprisonnement soit immédiatement libéré et que les charges retenues contre lui soient abandonnées - Amnesty International (Amnesty International, 2023)
À l’approche du procès en appel, jeudi 13 juillet 2023, de Truong Van Dung, défenseur des droits humains condamné pour « propagande contre le gouvernement » et condamné à six ans d’emprisonnement en mars 2023 uniquement pour avoir exprimé librement ses opinions, Ming Yu Hah, directrice régionale adjointe pour le travail de campagne à Amnesty International, a déclaré : « Les autorités vietnamiennes utilisent une fois de plus à mauvais escient le système pénal pour réprimer la dissidence. Truong Van Dung, qui a été arrêté pour avoir donné des interviews à des médias, n’aurait jamais dû être emprisonné. Les autorités vietnamiennes doivent abandonner les accusations fallacieuses retenues contre lui et le libérer immédiatement et sans condition.
Keywords: 2023-07 July

Nigeria. Les autorités doivent agir immédiatement pour sauver des vies face au risque d’inondations meurtrières - Amnesty International (Amnesty International, 2023)
Les autorités nigérianes doivent sans attendre prendre des mesures concrètes pour se préparer aux crues et en atténuer les conséquences potentielles.
Keywords: 2023-07 July

Tunisie. Les droits humains en danger deux ans après l’accaparement du pouvoir par le président Kaïs Saïed - Amnesty International (Amnesty International, 2023)
Au cours de la deuxième année qui s’est écoulée depuis l’accaparement du pouvoir par le président Kaïs Saïed, les autorités tunisiennes ont poursuivi sur la voie de la répression en emprisonnant des dizaines d’opposant·e·s politiques et de détracteurs et détractrices du régime, bafoué l’indépendance du pouvoir judiciaire, supprimé des garanties institutionnelles en matière de droits humains et incité à la discrimination à l’égard des personnes migrantes, a déclaré Amnesty International le 24 juillet 2023. « Décret après décret, attaque après attaque, le président Kaïs Saïed, avec son gouvernement, a considérablement porté atteinte au respect des droits humains en Tunisie depuis qu’il s’est accaparé le pouvoir en juillet 2021. Ce faisant, il a privé les Tunisien·ne·s de droits élémentaires qu’ils avaient obtenus de haute lutte et a alimenté un climat de répression et d’impunité. Il faut que les autorités tunisiennes inversent immédiatement cette trajectoire dangereuse et respectent leurs obligations internationales en matière de droits humains », a déclaré Heba Morayef, directrice du programme Afrique du Nord et Moyen-Orient à Amnesty International.
Keywords: 2023-07 July; Kaïs Saïed

Russia: Investigate vicious attack on Elena Milashina and Aleksandr Nemov in Chechnya - Amnesty International (Amnesty International, 2023)
The vicious beating of Elena Milashina and Aleksandr Nemov by masked assailants in Chechnya this morning was an abhorrent act of violence that must not go unpunished
Keywords: 2023-07 July; Chechnya; Tchétchénie

Netherlands: 'Historic victory' as law amended to recognize that sex without consent is rape - Amnesty International (Amnesty International, 2023)
Responding to the news that the Netherlands’ House of Representatives has voted to amend the Sexual Offences Act by introducing a consent-based definition of rape.
Keywords: 2023-07 July

Russie. Il faut enquêter sur l’agression dont ont été victimes Elena Milachina et Alexandre Nemov en Tchétchénie - Amnesty International (Amnesty International, 2023)
Le passage à tabac d’Elena Milachina et d’Alexandre Nemov par des assaillants masqués en Tchétchénie est un acte de violence qui ne doit pas rester impuni.
Keywords: 2023-07 July; Chechnya; Tchétchénie

Afrique: La lutte contre la corruption en péril : Répression à l’encontre de défenseur·e·s anticorruption en afrique de l'ouest et du centre – version courte - Amnesty International (Amnesty International, 2023)
Ce rapport présente les éléments de preuve les plus récents sur la répression féroce frappant les DDH qui luttent contre la corruption en Afrique de l’Ouest et du Centre, une région où de tels faits sont rarement signalés et qui est marquée par une culture d’impunité et par un non-respect de l’obligation de rendre des comptes en cas de violations des droits humains. Il porte sur 19 pays dont s’occupe le bureau régional d’Amnesty International pour l’Afrique de l’Ouest et du Centre, et comprend 31 cas de répression à l’encontre de DDH luttant contre la corruption dans certains de ces pays.
Keywords: 2023-07 July; Human Rights Defenders; Middle Africa; Western Africa

Cambodia: Election takes place under cloud of human rights crisis - Amnesty International (Amnesty International, 2023)
The human rights situation in Cambodia has severely deteriorated since the last national election in 2018, Amnesty International’s interim Deputy Regional Director for Research Montse Ferrer said today, ahead of Sunday polls expected to be dominated by the ruling Cambodian People’s Party after the sole viable opposition group was blocked from participating. “Authorities in Cambodia have spent the past five years picking apart what’s left of the rights to freedom of expression, peaceful assembly and association. There is a growing crackdown on human rights in Cambodia. Many people feel that they are being forced to participate in this election despite their party of choice not being on the ballot.
Keywords: 2023-07 July; Government; Human Rights

In West and Central Africa, authorities must fight corruption and uphold the human rights of those who expose it - Amnesty International (Amnesty International, 2023)
West and Central African states must stop persecuting human rights defenders who expose corruption, bribery and abuse of office, and instead take concrete and effective measures to protect and support them, Amnesty International said today, in observing African Anti-Corruption Day. Today marks the 20th anniversary of the African Union Convention on Preventing and Combating Corruption.
Keywords: 2023-07 July; Human Rights Defenders; Middle Africa; Western Africa